Pembangunan Ekonomi Provinsi Bali Periode 2014-2020 Berdasarkan Peran Perempuan terhadap PDRB - Yuni Wulandari; Muhammad Arif (Penerbit Goodwood, 2022)
Purpose: This study aims to determine the effect of the Gender Development Index, Women's Life Expectancy and Average Length of Schooling for Women on the Gross Regional Domestic Product (GRDP) in the Regency/City of Bali Province in 2014-2020. This research is a quantitative research with documentation data collection method. The type of quantitative data in this study is in the form of secondary data obtained from the Central Statistics Agency (BPS). Methodology: The method used in this research is descriptive quantitative using panel data regression analysis in the Eviews 10 application. The most appropriate approach to determine the effect of the independent variable on the dependent variable is the Random Effect Model (REM). Results: Based on the effect validity test or t test, it is explained that the variable life expectancy of women (AHH) and the average length of schooling for women (RLS) affect the GRDP of the Regency/City of Bali Province in 2014-2020, while the Gender Development Index (IPG) variable does not. affect the GRDP of the Regency / City of Bali Province in 2014-2020. The government can provide more space for the equal contribution of men and women in the economic, social, educational and political fields. The government also needs to allocate the state budget to achieve gender equality so that men and women have equal access, participation and benefits in promoting development. The limitation of this study lies in the IPG which has no influence on the GRDP of the Province of Bali. While on the other hand, patrilineal culture is still very strong in Bali. The possible predictors of IPG still need to be studied further to be studied so that more comprehensive dimensions of IPG can be obtained. Contribution: The expected contribution in this research is that it can be used as consideration for policy makers in determining the right policies, especially those related to increasing the role of women for economic development in the Regency / City of Bali Province. For researchers and literature, the results of this study are expected to be reference material or literature and reading material on the role of women in economic development.